Pengendalian Kualitas Produk Strawberry Powder Pada PT Z Menggunakan Metode Seven Tools - Permata Putri, Putu Sri Ratu; Penindra, I Made Dwi Budiana; Utami, Ni Made Cyntia; Komaladewi, A. A. Istri Agung Sri; Juliana, Mia; Imanuel Sitanggang, Bryan Estavan (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2025)
The development of time and technology significantly impacts business competition. Companies strive to produce high-quality products to remain competitive. It is crucial to control the products they produce to achieve this goal. This is something that PT Z, as a company that consistently maintains the quality of its products and prioritizes customer satisfaction, should already be doing. However, in 2022, it was noted that one of their products, strawberry powder, experienced a decline in quality. This was evidenced by records from the quality control department and complaints from consumers, citing damaged labels, leaking packaging, and differences in color and taste compared to expectations. In light of these issues, this research aims to further analyze the root causes of defects using the seven tools method and provide recommendations for improvement in the form of the 5W + 1H to PT Z, to prevent similar defects from occurring in the future. Based on the analysis, it was found that the causes of defects are attributed to human factors, machinery, materials, environment, and methods used.